Institute for Hockey Research - Bracko, M. R.
The primary focus of the research is female hockey. The IHR was the first organization to present data-based research on elite female hockey players (Meetings of the American College of Sports Medicine, Orlando, FL., June 1998). The Institute for Hockey Research was the first organization to publish research on female hockey players: Bracko, M.R. On-ice performance characteristics of elite and non-elite female ice hockey players. (Journal of Strength and Conditioning Research, Vol 15, #1, pages 42 - 47, 2001.)